The initiatives supported by reward-based crowdfunding in Poland - Kędzierska- Szczepaniak, Angelika (Inicjatywy wspierane przez crowdfunding oparty na nagrodach w Polsce, 2018)
Crowdfunding is a type of financing that is popular not only among entrepreneurs. There are examples of financing sport, culture, music or just someone’s dreams, and many good projects could not have been realized without crowdfunding. The analysis of the largest projects realized on one of the Poland’s oldest and biggest Polish crowdfunding platform – polakpotrafi.pl will be made in the article. It will be the background to formulate some conclusions about the initiatives supported by reward-based crowdfunding platforms. It can be hypothesized that crowdfunding in Poland is developing rapidly but the value and number of projects is still lower than in Western Europe countries and the USA. The research methods used in the article are primarily a statistical and comparative method and case study analysis. The data from the European Commission, the World Bank and crowdfunding platforms will be used.
Management Sciences = Nauki o Zarządzaniu, 2018, vol. 23, no. 4; s. 18-27
Keywords: community; crowdfunding; CF platforms; reward-based crowdfunding